Two lives of Cyrano de Bergerac: for the 400th anniversary - Kozyrev, A.L. (Perm Federal Research Centre Journal, 2019)
The article describes Cyrano de Bergerac, a French poet and playwright, both as a real man and a literary character comparing the facts of his life and the plot of Edmond Rostand’s play. It also estimates his contribution to literature and science.